2011
DOI: 10.1007/s11302-011-9271-6
|View full text |Cite
|
Sign up to set email alerts
|

In pursuit of P2X3 antagonists: novel therapeutics for chronic pain and afferent sensitization

Abstract: Treating pain by inhibiting ATP activation of P2X3-containing receptors heralds an exciting new approach to pain management, and Afferent's program marks the vanguard in a new class of drugs poised to explore this approach to meet the significant unmet needs in pain management. P2X3 receptor subunits are expressed predominately and selectively in so-called C- and Aδ-fiber primary afferent neurons in most tissues and organ systems, including skin, joints, and hollow organs, suggesting a high degree of specifici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
145
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(152 citation statements)
references
References 171 publications
(186 reference statements)
2
145
0
5
Order By: Relevance
“…In addition, augmented release of transmitters, most notably ATP, from the urothelium can lead to painful sensations by excitation of purinergic receptors on sensory fibers both peripherally and centrally (43,56,267). Thus inhibition of purinergic P2X3 receptors has been shown to be effective in suppressing afferent excitation in various animal models and may be effective in clinical conditions associated with pain such as BPS/IC (101,113). Onabotulinum toxin A (BoNT-A) has been used in the treatment of lower urinary tract disorders including BPS/IC and appears to have a positive therapeutic effect (64).…”
Section: A Bladder Pain Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, augmented release of transmitters, most notably ATP, from the urothelium can lead to painful sensations by excitation of purinergic receptors on sensory fibers both peripherally and centrally (43,56,267). Thus inhibition of purinergic P2X3 receptors has been shown to be effective in suppressing afferent excitation in various animal models and may be effective in clinical conditions associated with pain such as BPS/IC (101,113). Onabotulinum toxin A (BoNT-A) has been used in the treatment of lower urinary tract disorders including BPS/IC and appears to have a positive therapeutic effect (64).…”
Section: A Bladder Pain Syndromementioning
confidence: 99%
“…In several animal models, selective dual P2X3, P2X2/3 antagonists have been shown to be effective at reducing nocifensive responses, hyperalgesia, and allodynia (150,151). New drugs are in development (101,102,113), but so far no clinical experiences have been published.…”
Section: G P2x3-receptor Antagonistsmentioning
confidence: 99%
“…With the recent discovery of innovative chemical scaffolds for P2X3 antagonists, the first Phase 2 "proof-of-concept" studies are currently underway for inflammatory, visceral, and neuropathic pain patients [28].…”
Section: 2)mentioning
confidence: 99%
“…), but by the use of various in vivo models for the pre-clinical study of these types of pain. It has proven to be extremely difficult to draw generalized conclusions based on in vitro or pre-clinical in vivo data, apart from one specific type of pain (visceral pain) where the P2X3 subtype plays a prominent role [28]. Moreover, the large number of P2 receptor subtypes involved (to which P1 receptors responding to adenosine should be added also) [3], and long-standing lack of selective ligands to clearly identify the roles of specific P2 receptor subtypes in preclinical studies has complicated the identification of specific purinergic targets.…”
Section: Progress Towards Therapeutic Interventionsmentioning
confidence: 99%
“…TNP-ATP [2-O-(2,4,6-trinitrophenyl)-ATP] (Jarvis et al, 2001), A-317491 (McGaraughty et al, 2003), and RO51 ) are P2X3/P2X2/3 antagonists that have shown reduced hyperalgesia and mechanical allodynia in inflammatory and neuropathic pain models. P2X3/P2X2/3 antagonists are currently being tested in the clinic, so their analgesic efficacy has yet to be established in patients (Ford, 2012). Progress in the discovery of novel analgesics has been hampered by limited predictability of efficacy from preclinical animal studies to validation in humans (Mogil et al, 2010).…”
Section: Introductionmentioning
confidence: 99%